Най-хубавият вкус е да живееш и твориш в родината. Писма на художничката Бронка Гюрова-Алшех до Донка и Константин Константинови - Душкова, Мира (Poznańskie Studia Slawistyczne, 2020)
The current article presents five letters from the Bulgarian artist Bronka Gyurova-Alcheh written in the period 1959–1968, addressed to the writer Konstantin Konstantinov and his sister – the artist Donka Konstantinova. The letters were found in the personal archive of Konstantinov, and bring to light interesting facts of the life in Buenos Aires of Bronka Gyurova, who emigrated from Bulgaria in 1951.